Elite student-athletes' perceptions of coaches' behavior during the 23rd World Universiade Games in Kazan, Russia - Hagan, J. E.; Ansah, E. W.; Pollmann, D.; Schack, T. (International Journal of Human Movement and Sports Sciences, 2017)
Despite the fact that behavior of coaches is critical towards optimal development and performance of athletes, there still remains a dearth of empirical evidence involving self-perceptions of competitive athletes at elite level. The purpose of the present study was to examine athletes' perceptions related patterns and gender differences specific to coaching behaviors during competition. Consequently, the Leadership Scale for Sports was administered to 201 conveniently sampled elite student-athletes during the 23rd World Universiade Games at Kazan, Russia. Results show that a considerable number of sampled athletes perceived their coaches not to have provided the needed social support and positive feedback during competition. However, majority of these athletes felt they were involved democratically across the competition period. Additionally, while male athletes perceived their coaches to have given appreciable training and instruction, were more democratic, socially supportive, and provided positive feedback, female athletes perceived their coaches to be autocratic. A greater need for social support and positive feedback are required from coaches to help athletes deal with the stressors of elite competition. Similarly, the gender differences in the athletes' perceptions suggest a more idiosyncratic approach and flexibility toward coaching at high performance level if desired outcomes are to be accomplished.